Sustained Nitric Oxide Release Using Hybrid Magnetic Nanoparticles for Targeted Therapy: An Investigation via Electron Paramagnetic Resonance - Rawan Salami; Ronit Lavi; Yifat Harel; Esthy Levy; Jean Paul Lellouche; Svetlana Gelperina; Rachel Persky (Journal of Nanotheranostics)
This research describes the development and thorough characterization of a novel, versatile, and biocompatible hybrid nanocarrier of the NO-releasing agent NOC-18, with a specific focus on optimizing the purification process. In this study, we focused on the sustained release of NO using biocompatible and diagnostic hybrid magnetic nanoparticles (hMNPs) containing cerium-doped maghemite (CM) NPs, embedded within human serum albumin (HSA) protein. A comprehensive study was conducted using electron paramagnetic resonance (EPR) alongside the Griess assay to evaluate NO release from the chosen NO donor, NOC-18, and to assess the limitations of the molecule under various reaction conditions, identifying the optimal conditions for binding NOC-18 with minimal NO loss. Two types of particles were designed: In-hMNPs, where NOC-18 is encapsulated within the particles, and Out-hMNPs, where NOC-18 is attached onto the surface. Our results demonstrated that In-hMNPs provided a sustained and prolonged release of NO (half-life, 50 h) compared to the rapid release for the Out-hMNPs, likely due to the strong bonds formed with cerium, which helped to stabilize the NO molecules. These results represent a promising approach to designing a dual-function agent that combines contrast properties for tumor MRI with the possibility of increasing the permeability of tumor vasculature. The employment of this dual-function agent in combination with nanotherapeutics could improve the latter’s efficacy by facilitating their access to the tumor.